Raw materials constraints in the handicraft sectors: experience from stone carving clusters of Orissa. (20th May 2009) - Panda, D.K.
The article analyses the supply chain of raw materials in the stone carving clusters of Orissa and highlights the major issues in the provision of raw material supply for carving such as quarrying, costing, irregularity and seasonality in supply and processing. In addition, the article analyses how the institutional and legal framework in stone quarrying and supplies. Under this study, various types of raw material along with their sources were discussed, the annual demand-supply gap for raw materials were calculated based on various parameters and how the government retains the control over quarrying, regulation, monitoring and marketing. The study also reflects how the demand of raw materials is met from official and unofficial sources. The article discusses the policy issues like how there is no concrete policy in the state regarding quarrying and supply of stone for artisans.